ORGANIZATION OF ACTIVITIES OF TEACHERS IN THE EDUCATIONAL PROCESS TAKING INTO ACCOUNT THE TECHNOLOGICAL CULTURAL COMPETENCE - Muborak Abdullaeva (Galaxy International Interdisciplinary Research Journal, 2022)
This article details the content of culture and technological culture, the role and function of "Technology" as a science and the most modern and effective methods, the organization of activities in the educational process, taking into account the competence of technological culture of teachers.